Acute effect of antiseizure drugs on background oscillations in Scn1aA1783V Dravet syndrome mouse model - Quinn, Shir; Brusel, Marina; Ovadia, Mor; Rubinstein, Moran (Frontiers in Pharmacology, 2023)
Dravet syndrome (Dravet) is a rare and severe form of developmental epileptic encephalopathy. Antiseizure medications (ASMs) for Dravet patients include valproic acid (VA) or clobazam (CLB) with or without stiripentol (STP), while sodium channel blockers like carbamazepine (CBZ) or lamotrigine (LTG) are contraindicated. In addition to their effect on epileptic phenotypes, ASMs were shown to modify the properties of background neuronal activity. Nevertheless, little is known about these background properties alternations in Dravet. Here, utilizing Dravet mice (DS, Scn1aA1783V/WT), we tested the acute effect of several ASMs on background electrocorticography (ECoG) activity and frequency of interictal spikes. Compared to wild-type mice, background ECoG activity in DS mice had lower power and reduced phase coherence, which was not corrected by any of the tested ASMs. However, acute administration of Dravet-recommended drugs, VA, CLB, or a combination of CLB+STP, caused, in most mice, a reduction in the frequency of interictal spikes, alongside an increase in the relative contribution of the beta frequency band. Conversely, CBZ and LTG increased the frequency of interictal spikes with no effect on background spectral properties. Moreover, we uncovered a correlation between the reduction in interictal spike frequency, the drug-induced effect on the power of background activity, and a spectral shift toward higher frequency bands. Together. these data provide a comprehensive analysis of the effect of selected ASMs on the properties of background neuronal oscillations and highlight a possible correlation between their effect on epilepsy and background activity.